Associations of knee extensors muscle fiber conduction velocity with muscle strength qualities in elite female handball players - Kurz, E.; Brehme, K.; Gizzi, L.; Pröger, S.; Schwesig, R.; Delank, K. S.; Bartels, T. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Recently it has been shown that in professional female handball players the muscle fiber conduction velocity (MFCV) of the vastus medialis (VM) muscle was at different contraction intensities consistently higher than its lateral counterpart. Higher MFCV suggests muscle fibers with a larger cross-sectional area being recruited. During fast ballistic contractions forces developed per unit time are determined by the recruitment of higher threshold motor units. Thus, the aim of this study was to prove the relationship between MFCV and the rate of force development (RFD). We hypothesized that the VM MFCV would predict the RFD but that the vastus lateralis (VL) MFCV would not. METHODS: Twenty-two elite female handball players (age: 17-30 years, BMI: 21-28 kg/m²) participated in this cross-sectional study. MFCV of the VM and VL muscles was recorded in monopolar mode (EMG-USB2+, OT Bioelettronica, sampling rate: 2048/s) using a linear electrode array (ELSCH004, Spes Medica) at 100% contraction intensity concurrently with isometric force (SM-2000N, Forza, gain: 200), during the pre-season screenings, at their dominant side. The dominant lower limb was defined as the preferred side used for takeoff actions. After a brief warm-up and familiarization, two RFD trials were recorded followed by two maximum voluntary contraction (MVC) measurements, each after one minute pause. The maximum MVC values and RFD at 100 ms were scaled to athletes` leg length and body mass, resulting in maximum voluntary torque (MVT) or rate of torque development (RTD) per unit body mass. Linear regression analyses were applied to examine the relationships of VM or VL MFCV with MVT or RTD. RESULTS: All variables were normally distributed (p > 0.2). The female handball players revealed on average a maximum strength of 3.2 (SD 0.5) Nm/kg. The explosive strength at 100 ms ranged from 1.1 to 2.3 Nm/kg. However, MFCV was not related to maximum (VM: r = -0.07, p > 0.7; VL: r = 0.02, p > 0.9) nor explosive strength (VM: r = 0.08, p > 0.7; VL: r = 0.30, p = 0.2). CONCLUSION: The variation of the normalized maximum or explosive strength in elite female handball players cannot be explained with the MFCV of the knee extensors. The contraction type used or the diverse muscle fiber composition in team sport athletes possibly account for these results. In turn, these findings suggest that MFCV measurements alone are not appropriate to estimate muscle strength qualities, particularly in female handball players.